PROTECTION OF THE ENVIRONMENT IN WHICH LAND IS FERTILIZED BY THE APPLICATION OF BIOLOGICAL FERTILIZER - Sherqoziyeva G. F.; Bahriddinova M. N.; Egamberdiyeva Z. Z.; Boysariyeva M. R.; Toshpulatov B. M.; Abdurashidova D.; Rasulov R. S. (The Conference Hub, 2025)
One out of every 4 people on Earth is dressed and fed at the expense of the additional harvest that is being received at the expense of mineral fertilizers. The fact that 50% of the additional harvest from agricultural crops is due to fertilizers also requires an approach to them based on scientifically based recommendations, knowledge of their obtainment, properties and properties, and the specifics of storage. It is known that most agricultural crops are highly demanding on nitrogen. At the same time, their use has a negative impact not only on environmental pollution, but also on the storage of residues in the composition of agricultural products, as well as on public health. in agriculture 1.5 billion. tons of organic fertilizers are also used. Nitrogen deficiency slows down the synthesis of protein, enzyme, chlorophyll substances, while carbohydrate synthesis does not take place without chlorophyll. Nitrogen, which is important to its emerging cells, is a much-needed element during the growth and development of plants and, most importantly, at harvest end. For high yields from agricultural crops, 150-350, even up to 400 kg of pure nitrogen is required. One of the most basic ways to solve the nitrogen problem is to increase biological nitrogen in the soil, and it is advisable to use rain worms, nitrogen-scavenging microorganisms, and leguminous plants [2.3].